Konno Rastan Aortoventriculoplasty: The Last Resort for Complex Left Ventricular Outflow Tract Obstruction. - Timala, Rabindra Bhakta; Aryal, Marisha; Joshi, Dharmendra; Timala, Tisa; Pathak, Seejan; Rajbhandari, Nivesh; Pokhrel, Biswo; Basnet, Nishes; Joshi, Rheecha; Gautam, Navin (Nepalese Heart Journal, 2024)
Konno-Rastan aorto-ventriculoplasty is used to enlarge the aortic root in patients with a narrow aortic root that increases the size of the implanted valve. We present the two case reports; one 13-year-old male and another 59-year-old female, who underwent aortic valve replacement and double valve replacement respectively, along with Konno-Rastan aorto-ventriculoplasty. The case reports show that the Konno procedure allows for inserting an appropriately sized prosthesis in case of a small aortic annulus. The Konno technique addresses all levels of Left Ventricular Outflow Tract obstruction, increasing the left ventricular outflow tract more than other techniques. Both of the cases had good long-term follow-up.